Analysis of the motivational processes involved in university physical activity - Durán-Vinagre, Miguel Ángel; Ibáñez, Sergio J.; Feu, Sebastián; Sánchez-Herrera, Susana (Frontiers in Psychology, 2023)
This study analyzed university students’ motivational processes and intention to be physically active when engaging in physical activity (PA) according to gender and fields of study. A total of 1.524 subjects participated in the study, 61.9% (n=944) of whom were female and 38.1% (n=580) were male, with an average age of 19.61 years. The fields of study consisted of Arts and Humanities (n=118), Science (n=132), Health Sciences (n=351), Engineering and Architecture (n=196) and Social and Legal Sciences (n=727). The instruments used were the Behavioral Regulation in Exercise Questionnaire (BREQ-3) and the Intention to be Physically Active in the University Context (MIFAU) measurement scale. The results showed statistically significant differences in favour of men (p<0.01) in terms of intrinsic, integrated, identified, and introjected regulation of PA. Similarly, men were more likely to be physically active in the future than women (p<0.001). In terms of the study variables relating to the fields of study, statistically significant differences were obtained in the case of both more self-determined behavior (intrinsic, integrated and identified regulation) and amotivation (p<0.001). Finally, it was concluded that there is a need for the promotion of intervention strategies to encourage young adults to take up sporting activities as a means of preventing noncommunicable diseases, thereby avoiding the negative consequences of a sedentary lifestyle, physical inactivity, or abandonment of such activities.